2005
DOI: 10.1029/2005gb002482
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phytoplankton on the biogeochemical cycling of iron in subantarctic waters southeast of New Zealand during FeCycle

Abstract: During austral summer 2003, we tracked a patch of surface water infused with the tracer sulfur hexafluoride, but without addition of Fe, through subantarctic waters over 10 days in order to characterize and quantify algal Fe pools and fluxes to construct a detailed biogeochemical budget. Nutrient profiles characterized this patch as a high‐nitrate, low‐silicic acid, low‐chlorophyll (HNLSiLC) water mass deficient in dissolved Fe. The low Fe condition was confirmed by several approaches: shipboard iron enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 67 publications
(116 reference statements)
7
55
0
Order By: Relevance
“…Chlorophyll levels also increased in both the FeCycle patch [ Boyd et al , 2005] and throughout the survey region as seen by MODIS‐AQUA (Figure 3). In patch discrete sampling showed a doubling in the chlorophyll content from 0.4 to 0.8 μ g L −1 of the surface waters during FeCycle [ McKay et al , 2005]. This increase continued after FeCycle as Satellite chlorophyll estimates for 17 February show chlorophyll concentrations in the study region rising to over 1 μ g L −1 overall and included some areas near 2 μ g L −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll levels also increased in both the FeCycle patch [ Boyd et al , 2005] and throughout the survey region as seen by MODIS‐AQUA (Figure 3). In patch discrete sampling showed a doubling in the chlorophyll content from 0.4 to 0.8 μ g L −1 of the surface waters during FeCycle [ McKay et al , 2005]. This increase continued after FeCycle as Satellite chlorophyll estimates for 17 February show chlorophyll concentrations in the study region rising to over 1 μ g L −1 overall and included some areas near 2 μ g L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The beam attenuation coefficient ( c p ) data were used as a proxy for Particulate Organic Carbon (POC) [ Gardner et al , 2003] to examine whether the increase in chlorophyll observed during FeCycle [ McKay et al , 2005] was related to admixing with higher chlorophyll containing waters from outside the initial SF 6 patch. During the first 2 phases of patch evolution a mixing gradient for POC between the initial SF 6 patch ( c p ∼ 0.08) and out patch waters ( c p > 0.08) was apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Size-fractionated chlo rophyll a (chl a) concentrations (chl a retained on 0.2, 2.0, and 20.0 µm pore size polycarbonate filters) were calculated as the arithmetic mean of measurements from duplicate samples from individual bottles using the non-acidification approach (Welschmeyer 1994). Dissolved nutrients (NO 3 , PO 4 , SiO 3 ) were determined by shipboard automated analysis (after Frew et al 2001), and photosynthetic efficiency (F v /F m ) values were determined as the mean of 5 repeated measures using fast repetition rate fluorometry as described by McKay et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment bioassays, though offering direct experimental evidence for growth limitation, do not completely mimic the undisturbed natural environment: grazing is disrupted, physical mixing is decreased, and the phytoplankton are isolated at a fixed optical depth [59]. To overcome these concerns, several biochemical and molecular approaches have been suggested such as monitoring the expression of Feresponsive genes in environmental samples [60,61], measuring the ratios of the redox catalysts ferredoxin:flavodoxin [62,63] or other suitable Fe-responsive proteins such as IdiA [64], and assaying variable chlorophyll fluorescence [65]. Implementing a living system such as a bioreporter organism can help us gain a better understanding of the availability of Fe from the perspective of a living cell.…”
Section: Bioreporters Of Trace Metal Availability: Fementioning
confidence: 99%
“…While the use of Fe-responsive bioreporters has offered some evidence of transient Fe deficiency in the Great Lakes (e.g., [9,62]), it is not widespread [35,46]. A new approach whereby the bioreporter is contained in a porous underwater chamber (PUC) during incubation with unfiltered water [44] promises to offer insight into the biological cycling of Fe by regenerative processes such as grazing and viral lysis which may provide 30-80% of the algal Fe demand in surface seawater [62].…”
Section: Bioreporters Of Trace Metal Availability: Fementioning
confidence: 99%